The Role of Restriction in Motivation of Winter Sports Tourists in the Alvares Ski Resort in Ardabil Province - Sadaf Hesari; Nasrin Azizan Kohan (Research in Sport Management and Marketing)
Purpose: Winter sports tourism is a key economic factor in many mountain regions worldwide. Motivation has a very strong effect on the behavior of tourists. Therefore, motivations act as travel stimuli, and in contrast, restrictions are factors that prevent the participation and presence of tourists in related activities. The purpose of this study is to investigate the role of restrictions in motivating winter sports tourists to Alvares ski resort in Ardabil province.Methods: This research is descriptive-type and in terms of purpose, it is practical, also, the field research is used in this study. The statistical population of this study is all sports tourists and ski tourists in Ardabil province and the statistical sample based on Morgan sampling table. 370 people were selected as the statistical sample. In this study, in order to analyze the data, statistical methods of frequency distribution, mean and standard deviation and simple regression test have been used.Results: The results show that in general, the restrictions have a significant effect on the motivation of tourists (P = 0.01).Conclusion: As a result of reducing tourist restrictions, both directly and through its relationship to the level of motivation of tourists, ski resort managers should be considered to retain and attract customers.